RETRACTED: Biological resources of Lake Kroshnozero (North-West of Russia) - Syarki Maria; Sidorova Anastasia; Georgiev Andrey; Slastina Julia (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001